PENGARUH LATIHAN MOVING TARGET TERHADAP PUKULAN FOREHAND DRIVE PADA KLUB TENIS BHINEKA BUNGO - Hasnah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Abstract This research started from the existence of several problems, namely the Bhineka Tennis Club Bungo players still had deficiencies in hitting Forehand drives. This can be seen when practicing or playing when the enemy gives the ball towards the forehand, the Bungo Tennis Club's Bhineka Tennis players often make mistakes or die alone. This study aims to determine whether there is an effect of Moving Target Exercise on Forehand Drive Shots at the Bhinika Bungo Tennis Club. This type of research is an experiment with the design